Comparison between Different Perforator Imaging Modalities for the Anterolateral Thigh Perforator Flap Transfer: A Prospective Study - Ritschl, Lucas M.; Fichter, Andreas M.; Bomhard, Achim von; Koerdt, Steffen; Kehl, Victoria; Kolk, Andreas; Wolff, Klaus-Dietrich; Grill, Florian D. (Journal of Reconstructive Microsurgery, 2020)
Background Perforator imaging is routinely performed before perforator flap harvest. Hand-held Doppler (hhD) and color duplex ultrasonography (CDU) are currently the most popular radiation-free methods for this purpose that can be applied by the surgeon alone. The aim of this study was to compare the accuracy, reliability, and feasibility of hhD and CDU with indocyanine green angiography (ICGA) in the anterolateral thigh perforator flap (ALTPF).Methods All consecutive ALTPF procedures between May 2017 and April 2018 were included in this prospective study. The perforators were visualized by three investigators independently and randomized, applying hhD, CDU, and ICGA. The presence and the distance to the identified perforator were registered. Further, body mass index (BMI), American Society of Anesthesiologists-status, and the patient's history regarding smoking, alcohol use, and diabetes mellitus were registered alongside gender and age to analyze possible confounders.Results A total of 12 patients were enrolled with a median age of 67 (52–87) years. In total, 30 perforators were detected intraoperatively as well as with the ICGA. The latter visualized the perforators significantly more precisely than hhD and CDU (p < 0.001 and p = 0.001). The sensitivity and positive predictive value were 67 and 62% for hhD, 73 and 64% for CDU, and 100 and 100% for ICGA, respectively.Conclusion According to this study, ICGA visualized perforators more accurately than the standard methods hhD and CDU. Further, it was associated with the highest sensitivity and positive predictive value. ICGA consistently delivered excellent results, whereas hhD and CDU showed variability.
Keywords: ALT perforator flap; perforator imaging; ICG angiography